Resistance Response of Chilli (Capsicum annuum L.) F1 to Fusarium oxysporum Involves Expression of the CaChi2 Gene - Rejeki Siti Ferniah,; Rina Sri Kasiamdari,; Achmadi Priyatmojo,; Budi Setiadi Daryono, (Tropical Life Sciences Research, 2018)
Cross-breeding is a method of producing progeny with better resistance to pathogens. Resistance to pathogens usually involves pathogenesis-related (PR) proteins. Class II chitinase is an example of a defensive PR protein in plants. The class II chitinase in chilli is coded by the CaChi2 gene. In this study, we crossed susceptible with resistant chilli cultivars, analysed the F1 resistance response against pathogenic F. oxysporum, and analysed the level of CaChi2 gene expression in the F1. Data were collected using disease severity index (DSI) determination and gene expression analysis by qRT-PCR (quantitative Reverse Transcriptase Polymerase Chain Reaction). Results showed that the DSI of F1 was not significantly different from the resistant ancestor. The relative CaChi2 expression level of F1 was higher than the susceptible ancestor but not significantly different from the resistant ancestor. We concluded that the F1 can be categorised as resistant to F. oxysporum, and the CaChi2 gene is involved in the molecular defense response.ansformed gelatins.